Development of a specialty medication clinical dashboard to improve tumor necrosis factor-α inhibitor safety and adherence monitoring - Hu, Anna M; Pepin, Marc J; Hashem, Mohamed G; Britt, Rachel B; Britnell, Sara R; Bryan, William E; Brown, Jamie N (American journal of health-system pharmacy, 2022)
To describe the development of a pilot specialty medication clinical dashboard targeting tumor necrosis factor (TNF)-α inhibitor therapy. This was a quality improvement project conducted between August 2019 and April 2020. The dashboard was designed with collaboration between clinical pharmacists and specialty providers in rheumatology, gastroenterology, and dermatology. Data was queried from the Veterans Affairs Corporate Data Warehouse. Patients with an active prescription or intravenous order for a TNF-α inhibitor were included. Dashboard flag criteria focused on TNF-α inhibitor safety and adherence monitoring. Flag results from the dashboard were characterized from data captured at a single time point. For 431 patients on TNF-α inhibitor treatment at the institution, 304 flags corresponding to 223 unique patients (51.7%) were identified on the dashboard: 3% of patients had a new infection, 9% had overdue monitoring laboratory tests, 5% had a critical laboratory result, 2% were on 2 biologic agents, 27% were overdue for a refill, 6% had an emergency department visit, and 2% had an inpatient admission. No patients were flagged for heart failure exacerbation or new malignancy. Seventeen percent of patients were prescribed high-dose etanercept or adalimumab, representing a potential annual cost savings of $302,497 if 50% of these patients had their dose successfully reduced to labeled dosing. Opportunities for pharmacist intervention utilizing the dashboard were identified and characterized through chart review of flagged patients. Pharmacists have the opportunity to improve safety and adherence for TNF-α inhibitor therapy through use of a specialty medication clinical dashboard. The dashboard should be used in conjunction with collaborative practice protocols.